Towards A Compulsory Insurance Of The Civil Liability Of The Doctor (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The idea of ​​the research revolves around the obligatory insurance of civil liability of the physician; As this insurance is considered a form of insurance on civil liability in general، this type of insurance has become widespread in the medical community، and it remains in some countries، including Syria، as voluntary insurance subject to the principle of authority of the will، but the increased risks resulting from medical work as a result of using Sophisticated machines in surgical operations of all kinds، and the development of new medical fields، have led legislators in many countries such as France، Algeria and the United Arab Emirates to make this type of insurance compulsory، They considered it as a condition for practicing the profession، and supported the texts of the compulsory insurance with deterrent penalties to ensure its respect by the taxpayers. The legislature accepted mandatory texts. At the end of the research، we reached a set of conclusions، the most important of which are: that the Syrian law did not stipulate special rules for medical liability، and that it had not yet adopted the compulsory insurance system with regard to the civil liability of the doctor; This is in contrast to some laws of other countries، such as French، Algerian and Emirati law. We also recommended in this research the need for the Syrian legislator to enact special rules for medical responsibility that are commensurate with the specificity of medical work، and to oblige doctors to insure their civil responsibility towards patients; Similar to the legislation of other countries، the insurance system achieves a double protection for the insured (the doctor) and the injured (the patient). It also helps to spread insurance awareness and the prosperity of this important sector from an economic point of view.